Generating New Cross‐Relaxation Pathways by Coating Prussian Blue on NaNdF4 To Fabricate Enhanced Photothermal Agents. (17th May 2019) - Yu, Zhongzheng; Hu, Wenbo; Zhao, Hui; Miao, Xiaofei; Guan, Yan; Cai, Weizheng; Zeng, Zhiping; Fan, Quli; Tan, Timothy Thatt Yang
Abstract: Cross‐relaxation among sensitizers is commonly regarded as deleterious in fluorescent materials, although favorable in photothermal agents. Herein, we coated Prussian blue (PB) on NaNdF4 nanoparticles to fabricate core–shell nanocomplexes with new cross relaxation pathways between the ladder‐like energy levels of Nd 3+ ions and continuous energy band of PB. The photothermal conversion efficiency was improved exceptionally and the mechanism of the enhanced photothermal effect was investigated. In vivo photoacoustic imaging and photothermal therapy demonstrated the potential of the enhanced photothermal agents. Moreover, the concept of generating new cross‐relaxation pathways between different materials is proposed to contribute to the design of all kinds of enhanced photothermal agents. Abstract : Blau blüht der Nanopartikel : Durch die Beschichtung von NaNdF4 ‐Nanopartikeln mit Berliner Blau wurden Kern/Schale‐Nanokomplexe mit neuen Kreuzrelaxationspfaden zwischen den diskreten Energieniveaus der Nd 3+ ‐Ionen und dem kontinuierlichen Energieband des Berliner Blau hergestellt. Hierdurch erhöht sich die photothermale Konversionseffizienz drastisch. Photoakustische Bildgebung und photothermale Therapie belegen in vivo das Potential der Nanokomplexe.